HISTORY OF DEVELOPMENT OF MODERN UZBEK LITERATURE - Ibatova Klara Raxmatullayevna (Bright Mind Publishing, 2025)
Modern Uzbek literature has come a long and difficult way. In this article, the author comprehensively reflects on the history of the development of modern Uzbek literature and its modern development.
Keywords: Modern literature, literary traditions, Uzbek literature, new stage, forms and contents of literature.